Targeting MDM2, RAS, and PCNA for cancer targeted therapy: pan-cancer approaches vs. cancer-specific strategies - Wang, Wei; Alley, Abigail; Sun, Na; Tadesse, Meheret; Wang, Xinshi; Zhang, Ruiwen (Frontiers in Pharmacology, 2025)
Cancer therapy and cancer drug discovery and development have been historically focused on specific cancers (tissue/organ of origin). However, with advances in molecular biology and multi-omics of cancer, there is a trend to develop pan-cancer therapeutic modalities. In targeted therapy, pan-cancer strategies target common molecular alterations across different cancer types and specific cancer strategies are tailored to the unique biological characteristics of individual tumor types. Each approach offers distinct advantages and limitations, and understanding these differences is critical in the era of precision oncology. Targeting key molecular drivers in cancer has significantly changed drug development, allowing for broad-spectrum therapeutic strategies that address shared oncogenic pathways across various tumor types. Among these drivers, RAS, PCNA, and MDM2 have become critical targets due to their roles in a broad-spectrum of cancer biology, e.g., cell proliferation, survival, and genomic stability. Advances in molecularly guided therapies have led to promising approaches for disrupting these pathways, offering new opportunities for cancer treatment. Despite significant progress in the past, challenges such as drug resistance, tumor heterogeneity, and toxicity remain obstacles to widespread clinical success. This review explores the historical development, current advancements, and future directions of RAS, PCNA, and MDM2-targeted therapies, emphasizing their potential to reshape cancer treatment through pan-cancer approaches using biomarker-driven technologies, combination strategies, and next-generation inhibitors. These advancements pave the way for more effective and durable therapies across a wide range of malignancies.